DC & Hybrid Micro-Grids - Mihet-Popa, Lucian; Saponara, Sergio; Saletti, Roberto (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book is a printed version of the papers published in the Special Issue "DC & Hybrid Microgrids" of Applied Sciences. This Special Issue, co-organized by the University of Pisa, Italy and Østfold University College in Norway, has collected nine papers and the editorial, from 28 submitted, with authors from Asia, North America and Europe. The published articles provide an overview of the most recent research advances in direct current (DC) and hybrid microgrids, exploiting the opportunities offered by the use of renewable energy sources, battery energy storage systems, power converters, innovative control and energy management strategies.